Polyester base film for photovoltaic backsheet, preparation method and application thereof
By using a mixture of ZIF-8 limited-domain metal particles and nanosilicon dioxide in the upper and lower surface layers of the photovoltaic backplane, combined with fillers such as titanium oxide and silica, the problem of weakening infrared reflection effect of black photovoltaic backplane is solved. Improves reflective performance and yellowing resistance, improves power generation efficiency and reduces production costs.
Patent Information
- Application Number
- CN202410658683.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-27
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2044-05-27
AI Technical Summary
The infrared reflection effect of existing black photovoltaic back panels is weakened during use, resulting in heat absorption and heating, reducing power generation power, and expensive reflective fillers are not suitable for use in production.
Polyester base film is used, including the upper and lower surface layers. The support layer is made of PET and PP. The upper surface layer is a mixture of ZIF-8 limited-domain metal particle material and nano-silicon dioxide. The lower surface layer is titanium oxide and dioxin Silicon oxide and other fillers are prepared through injection molding process to improve infrared reflection and yellowing resistance.
It effectively improves the infrared reflection performance and yellowing resistance of the photovoltaic backplane, avoids heat absorption and heating, improves power generation efficiency, and reduces production costs.
Abstract
Description
Technical Field
[0001] The present application relates to the field of new material technology, and specifically to a polyester base film for photovoltaic backplanes, a preparation method and applications thereof. Background Art
[0002] With the booming development of distributed photovoltaics, the market has put forward new requirements for the appearance design of modules, especially the consistency of color. Therefore, black modules are becoming more and more popular due to their beautiful appearance, especially in roof and facade installation. Conventional black photovoltaic backsheets can hardly form effective reflection of solar waves, which not only has limited effect on the power generation gain of the module, but also the backsheet easily absorbs heat and heats up, reducing the power generation of the module, and is prone to deformation after long-term use.
[0003] Improvements to black photovoltaic backsheets usually focus on increasing the reflectivity of the backsheet, especially the reflection of light waves in the near-infrared band, so as to reduce the heat absorption of the backsheet and increase the power generation of photovoltaic modules. Some black photovoltaic backsheets use a special coating design, in which an infrared reflective coating is applied to the surface of the photovoltaic backsheet. The problem is that the coating is easily worn out with the use of the photovoltaic module, which weakens the infrared reflection effect.
[0004] Infrared reflective fillers are usually added to the backplane film, but their infrared light reflection effect is affected by the stability, fusion, particle size, and particle structure of the filler. In actual production, the stability and economic benefits of the photovoltaic backplane film preparation also need to be considered. Some fillers with good reflective effects but high prices are not suitable for use in production. Summary of the invention
[0005] The purpose of this application is to improve the infrared reflection performance of the polyester base film for photovoltaic backplane.
[0006] Another object of the present application is to improve the anti-yellowing performance of the polyester base film for photovoltaic backplanes.
[0007] To achieve the above objectives, the technical solution adopted in the present application is: to provide a polyester base film for photovoltaic backplane, comprising an upper surface layer, a support layer and a lower surface layer, the support layer is made of PET and PP, the upper surface layer is a PET material dispersed with a first filler, the lower surface layer is a PET material dispersed with a second filler, the second filler is a combination of any one or more of titanium oxide, silicon dioxide, vanadium oxide, and bismuth oxide, and the first filler is a mixture of ZIF-8 confined metal particle material and nano-silicon dioxide.
[0008] As a preference, the first filler is ZIF-8 confined metal particle material and nano-silicon dioxide material in a mass ratio of (1-2):1.
[0009] As another preference, the mass percentage of the first filler in the upper surface layer is 0.5% to 1%.
[0010] As another preference, the metal particles in the ZIF-8 confined metal particle material are a combination of one or more of metal platinum, metal nickel, metal palladium or metal silver.
[0011] As another preference, the nano-silica material is a nano-silica material with surface modified carboxyl groups, and the preparation method of the nano-silica material with surface modified carboxyl groups is: dissolving glutaraldehyde and (3-aminopropyl)triethoxysilane in an organic solvent to obtain a first mixture, adding nano-silica and water to the organic solvent to obtain a second mixture, adding the second mixture to the first mixture, filtering the formed precipitate, washing, and drying to obtain the nano-silica material with surface modified carboxyl groups.
[0012] As another preference, the particle size of the nano-silicon dioxide is 30 to 60 nm.
[0013] As another preference, the thickness of the upper surface layer is 60-80 μm, the thickness of the support layer is 250-350 μm, and the thickness of the lower surface layer is 25-35 μm.
[0014] The present application also provides a method for preparing a polyester base film for photovoltaic backplane, comprising the following preparation steps: S1: preparing ZIF-8 using zinc salt and 2-methylimidazole, then adding the ZIF-8 into a metal salt solution and uniformly mixing to obtain a mixed solution, adding a reducing agent into the mixed solution to reduce metal ions to metal elements, filtering, drying and washing the precipitate to obtain a ZIF-8 confined metal particle material; S2: mixing the ZIF-8 confined metal particle material with a nano-silicon dioxide material to form a first filler, and the first filler is mixed with a PET masterbatch at a high speed and then injection molded to obtain an upper surface layer; S3: mixing the PET masterbatch with the PP masterbatch and then injection molded to obtain a support layer; mixing the nano-silicon dioxide with the PET masterbatch and then injection molded to obtain a lower surface layer; S4: co-extrude the upper surface layer, the support layer and the lower surface layer to obtain the polyester base film for photovoltaic backplane.
[0015] Further preferably, when the nano-silica material is surface-modified carboxyl-silica, the S2 step is specifically as follows: glutaraldehyde and (3-aminopropyl)triethoxysilane are dissolved in an organic solvent to obtain a first mixture, nano-silica and water are added to the organic solvent to obtain a second mixture, the second mixture is added to the first mixture, and the formed precipitate is filtered, washed, and dried to obtain the surface-modified carboxyl-silica nano-silica; the ZIF-8 confined metal particle material is mixed with the surface-modified carboxyl-silica nano-silica to form the first filler, and the first filler is mixed with the PET masterbatch at high speed and then injection molded to obtain the upper surface layer.
[0016] The present application also provides a photovoltaic cell, which includes, from top to bottom, a photovoltaic backplane, a packaging material, a battery cell, a packaging material and a packaging glass, wherein the photovoltaic backplane includes any of the above-mentioned polyester base films for photovoltaic backplanes, or the polyester base film for photovoltaic backplanes prepared by any of the above-mentioned preparation methods, and the upper surface layer is arranged on a side away from the battery cell.
[0017] Compared with the prior art, the beneficial effects of this application are:
[0018] (1) In the polyester base film for photovoltaic backsheet of the present application, a mixture of ZIF-8 confined metal particle material and nano-silicon dioxide material is used as the first filler, which can effectively improve the infrared light reflection performance and anti-yellowing performance of the polyester base film;
[0019] (2) In the polyester base film for photovoltaic backplane of the present application, a mixture of ZIF-8 confined metal particle material and surface-modified carboxyl-group nano-silicon dioxide material is used as the first filler, which can improve the compatibility of the first filler with PET and further improve the infrared light reflection performance and anti-yellowing performance of the polyester base film. DETAILED DESCRIPTION
[0020] Below, the present application is further described in conjunction with specific implementation methods. It should be noted that, under the premise of no conflict, the various embodiments or technical features described below can be arbitrarily combined to form new embodiments.
[0021] The terms "including" and "having" and any variations thereof in the specification and claims of this application are intended to cover non-exclusive inclusions. For example, a process, method, system, product or apparatus comprising a series of steps or units is not necessarily limited to those steps or units explicitly listed, but may include other steps or units not explicitly listed or inherent to these processes, methods, products or apparatuses.
[0022] The present application provides a polyester base film for a photovoltaic backplane, comprising an upper surface layer, a support layer and a lower surface layer, and the upper surface layer, the support layer and the lower surface layer are all white, so that the polyester base film for the photovoltaic backplane of the present application appears white, and a photovoltaic backplane of any color can be prepared, and the photovoltaic backplane has a good infrared reflection effect.
[0023] In some embodiments, after the polyester base film of the present application is prepared, a black surface layer is compounded on one or both sides of the polyester base film to form a black photovoltaic backplane, thereby achieving the infrared light reflection effect of the black photovoltaic backplane.
[0024] The upper surface layer is a PET material uniformly dispersed with a first filler, and the first filler is a mixture of ZIF-8 confined metal particle material and nano silicon dioxide.
[0025] In some embodiments, the mass ratio of ZIF-8 confined metal particle material to nano-titanium dioxide in the first filler is (1-2):1.
[0026] In some embodiments, the content of the first filler in the upper surface layer is 0.5% to 1%.
[0027] Zeolitic imidazolate frameworks (ZIFs) are an important subclass of metal-organic frameworks (MOFs). They have a structure similar to that of aluminosilicate zeolites, combining the advantages of both zeolites and MOFs. They not only have strong thermal and chemical stability, but also have high specific surface area and high pore volume. ZIFs are ordered porous materials formed by metal zinc ions and 2-methylimidazole connected by coordination bonds. They are widely used in many fields, including gas adsorption and separation, catalytic reactions, sensors, microelectronic devices, drug carriers, 3D printing, and fluorescence detection.
[0028] ZIF-8, the full name of which is Zeolitic Imidazolate Framework-8, is a kind of 2+ ) and 2-methylimidazole (2-MiM) to form a metal-organic framework (MOF) material. It is a type of zeolitic imidazolate framework (ZIFs) and has shown wide application potential in many fields due to its unique properties and structure.
[0029] ZIF-8 has many advantages: 1. High specific surface area: ZIF-8 has a large specific surface area, which makes it advantageous in fields such as adsorption, separation and catalysis. 2. Porous structure: The porous nature of ZIF-8 enables it to be used as a molecular sieve to effectively separate molecules. 3. Good biocompatibility: ZIF-8 shows good biocompatibility in the biomedical field and is suitable for applications such as drug carriers. 4. pH responsiveness: ZIF-8 can disintegrate in an acidic environment, which makes it possible to achieve targeted drug release in the tumor microenvironment (usually acidic). 5. Stability: ZIF-8 remains stable under physiological conditions, but disintegrates under acidic conditions. This property is very important for controlled drug release.
[0030] The infrared reflectivity of a material is affected by many factors, including but not limited to the material's composition, density, doping elements, particle size and morphology, surface treatment, and microstructure.
[0031] The infrared reflectivity of metal particles is affected by many factors, including particle size, shape, matrix refractive index, coating form, and particle arrangement. First, the size and shape of the particles have a significant effect on their infrared reflectivity.
[0032] First, the size and shape of the particles have a significant effect on the infrared reflectivity. Small metal particles absorb more strongly in the infrared region than large metal particles, which is related to surface plasmon resonance. In addition, the optical cross-section and scattering intensity of metal particles in different refractive index matrices will be affected, so the refractive index of the matrix is an important factor affecting the infrared reflectivity of metal particles.
[0033] The arrangement of metal particles also affects their infrared reflectivity. For example, a coating containing parallel-arranged flake metal ions has a lower emissivity, and this arrangement is affected by the solid content, size, coating thickness and resin absorption characteristics of the particles.
[0034] ZIF-8 has a diameter of approximately The hole and the six-ring window Taking advantage of the interconnected characteristics of the four-ring windows, nanometal particles can be evenly dispersed in the ZIF-8 carrier through liquid phase impregnation combined with in situ reduction. Moreover, the loading of metal particles does not change the morphology and size of ZIF-8, nor does it change the stability of ZIF-8.
[0035] ZIF-8 confined metal particles can effectively solve the dispersion problem of metal particles in PET without affecting the infrared reflection performance of metal particles. Evenly dispersing ZIF-8 with hollow confined metal particles in PET can solve the agglomeration problem of metal particles in PET. The evenly dispersed first reflective filler makes the first surface layer have good infrared reflection ability. When used in the photovoltaic backplane base film, a photovoltaic backplane with strong infrared reflection can be obtained, thereby avoiding the heating of the photovoltaic backplane and improving its photoelectric conversion efficiency.
[0036] In the polyester base film for photovoltaic backplane of the present application, the first filler is a mixture of ZIF-8 confined metal particle material and nano-titanium dioxide, wherein the metal particles confined in ZIF-8 are any one of platinum, nickel, palladium and silver.
[0037] In some preferred embodiments, the surface of nano-silica is modified with carboxyl groups to enhance its compatibility with ZIF-8 and polyester-based membranes, improve the interaction between nano-silica and ZIF-8 confined metal particle materials, and evenly disperse it in the upper surface layer to improve the infrared light reflection performance of the upper surface layer.
[0038] In addition, the surface modification of nano-silica with carboxyl groups can improve the compatibility of the first filler with PET, and avoid the peeling of the upper surface layer with the first filler added from the support layer, which would cause damage to the photovoltaic module and shorten the service life of the photovoltaic module.
[0039] In some embodiments, the particle size of nano-silicon dioxide is below 100 nm. In order to achieve better dispersion of the first filler in the upper surface layer, the particle size of nano-silicon dioxide is selected to be consistent with that of the ZIF-8 confined metal particle material.
[0040] In some preferred embodiments, the particle size of nano-silicon dioxide is 30-60 nm.
[0041] In some embodiments, the particle size of the ZIF-8 confined metal particle material is 30 to 60 nm.
[0042] In some embodiments, other additives are added to the upper surface layer, including a combination of one or more of a curing agent, a dispersant, and a plasticizer.
[0043] The support layer of the present application is a mixture of PET and PP. When PET is used outdoors for a long time, the water vapor and oxygen in the environment will corrode the backplane, causing it to lose its protection and support functions for the solar cell. PP resin has excellent barrier properties to water vapor and has a good barrier effect on the hydrolysis of PET.
[0044] The lower surface layer of the present application is a PET material with a second filler evenly dispersed therein. The second filler can be some oxides with good economic adaptability, such as titanium oxide, silicon dioxide, vanadium oxide, bismuth oxide, etc. The above oxides can exhibit lower absorption and higher reflection characteristics in the infrared band.
[0045] The lower surface layer is usually arranged on the side of the photovoltaic backplane base film facing the ground. Arranging a second filler in the lower surface layer can prevent the infrared rays reflected by the ground from causing the photovoltaic backplane to heat up. However, the infrared rays reflected by the ground are small after all, so a relatively cheap second filler is selected to have both practicality and cost-effectiveness.
[0046] In some preferred embodiments, the thickness of the upper surface layer is 60-80 μm, the thickness of the support layer is 250-350 μm, and the thickness of the lower surface layer is 25-35 μm.
[0047] The present application provides a method for preparing a polyester base film for a photovoltaic backsheet, comprising the following steps:
[0048] S1: ZIF-8 is prepared using zinc salt and 2-methylimidazole, and then ZIF-8 is added to a metal salt solution and mixed evenly to obtain a mixed solution, a reducing agent is added to the mixed solution to reduce the metal ions to metal elements, and the precipitate is filtered, dried and washed to obtain a ZIF-8 confined metal particle material;
[0049] S2: Mixing ZIF-8 confined metal particle material with nano-silicon dioxide material to form a first filler, and then mixing the first filler with PET masterbatch at high speed and then injection molding to obtain an upper surface layer;
[0050] S3: Mixing PET masterbatch and PP masterbatch and then injection molding to obtain a support layer; mixing nano-silicon dioxide and PET masterbatch and then injection molding to obtain a lower surface layer;
[0051] S4: The upper surface layer, the support layer and the lower surface layer are co-extruded to obtain the polyester base film for the photovoltaic backplane of the present application.
[0052] In some preferred embodiments, the nano-silica is nano-silica with surface modified with carboxyl groups. The specific preparation S2 is: glutaraldehyde and (3-aminopropyl)triethoxysilane are dissolved in an organic solvent to obtain a first mixture, nano-silica and water are added to the organic solvent to obtain a second mixture, the second mixture is added to the first mixture, and the formed precipitate is filtered, washed, and dried to obtain a material with nano-silica surface modified with carboxyl groups.
[0053] In some embodiments, the organic solvent is selected from N,N-dimethylformamide solution.
[0054] The present application also provides a photovoltaic cell, which includes, from top to bottom, a photovoltaic backplane, a packaging material, a battery cell, a packaging material and a packaging glass, wherein the photovoltaic backplane is made of the above-mentioned polyester base film for the photovoltaic backplane of the present application, and the upper surface layer of the polyester base film for the photovoltaic backplane is arranged on the side away from the battery cell.
[0055] Example 1
[0056] S1: Take 4.94mmol of Zn(NO3)2·6H2O and dissolve it in 100mL of methanol to obtain solution a, take 39.62mmol of 2-methylimidazole and dissolve it in 100mL of methanol to obtain solution b, quickly pour solution a into solution b, stir at room temperature for 1h, centrifuge the generated precipitate and wash it with methanol for 3 times, dry the washed precipitate at 60℃ for 12h to obtain a white powder, which is ZIF-8;
[0057] Take 49.52 mg of Ni(NO3)2·6H2O and dissolve it in 20 mL of deionized water. Then add 22.58 mg of polyvinyl alcohol (PVA). After stirring at room temperature for 1 h, add 200 mg of activated ZIF-8 into the solution and continue stirring for 2 h. In an ice-water bath, add 4.8 mL of NaBH4 dropwise to the solution. After the addition is complete, the solution continues to stir for 5 h. The resulting precipitate is centrifuged and washed 3 times with deionized water and dried at 60 °C for 12 h to obtain Ni@ZIF-8 material.
[0058] S2: The Ni@ZIF-8 material and nano-silicon dioxide with a particle size of 40 nm are uniformly mixed in a high-speed mixer at a mass ratio of 2:1. The mixture is the first filler. The first filler is mixed with the PET masterbatch at a high speed and then injection molded into a sheet sample at a pressure of 50 MPa and a temperature of 268°C by an injection molding machine. The mass proportion of the first filler is 1%, and an upper surface layer is obtained. The thickness of the upper surface layer is controlled to be 60-80 μm.
[0059] S3: melt-blending the PET masterbatch and the PP masterbatch in a mass ratio of 2:1, and sending the mixture into an injection molding machine for injection molding into a sheet sample at a pressure of 50 MPa and a temperature of 200°C to obtain a support layer, and controlling the thickness of the support layer to be 250-350 μm; stirring and mixing nano-silicon dioxide with a particle size of 40 nm with the PET masterbatch at a high speed, wherein the mass proportion of the nano-silicon dioxide is 1%, and sending the mixture into an injection molding machine for injection molding into a sheet sample at a pressure of 50 MPa and a temperature of 250°C to obtain a lower surface layer, and controlling the thickness of the lower surface layer to be 25-35 μm.
[0060] S4: The upper surface layer, the support layer and the lower surface layer are transported to the backplane co-extrusion production line and extruded through a mold to obtain a sheet-like melt. The sheet-like melt is cooled and shaped by a cooling roller, and then rolled or cut to obtain the polyester base film for the photovoltaic backplane of the present application.
[0061] Example 2
[0062] In this embodiment, a polyester base film for a photovoltaic backplane is prepared, wherein the content of the first filler is 1%, and the first filler is a mixture of Ag@ZIF-8 and nano-silicon dioxide in a mass ratio of 2:1.
[0063] The difference from the preparation method of Example 1 is that in step S1, the nickel salt is replaced by a silver salt.
[0064] Example 3
[0065] This embodiment prepares a polyester base film for photovoltaic backplane. The difference from Embodiment 1 is that in step S2, nano-silicon dioxide material with surface modified carboxyl groups is used instead of silicon dioxide. The other preparation steps are consistent with those in Embodiment 1.
[0066] S2: Preparation method of nano-silica surface modified carboxyl material: dissolving glutaraldehyde and (3-aminopropyl) triethoxysilane in N,N-dimethylformamide solution, stirring at 30-40°C for 2-5 hours to obtain a first mixture, adding nano-silica and water to the N,N-dimethylformamide solution, stirring at 0-40°C for 2-5 hours to obtain a second mixture, adding the second mixture to the first mixture and stirring for 5-6 hours, filtering the precipitate and washing it with N,N-dimethylformamide solution and methanol in turn, and drying to obtain the nano-silica surface modified carboxyl material;
[0067] The Ni@ZIF-8 material and the nano-silica surface modified carboxyl material are uniformly mixed in a high-speed mixer at a mass ratio of 2:1. The mixture is the first filler. The first filler is mixed with the PET masterbatch at a high speed and then injection molded into a sheet sample by an injection molding machine at a pressure of 50 MPa and a temperature of 268°C. The mass proportion of the first filler is 1%, and an upper surface layer is obtained. The thickness of the upper surface layer is controlled to be 60 to 80 μm.
[0068] Example 4
[0069] This embodiment prepares a polyester base film for photovoltaic backplane, which is different from the preparation method of Example 3 in that the nickel salt is replaced by a silver salt in step S1, that is, the first filler of Example 4 is a mixture of Ag@ZIF-8 material and nano-silicon dioxide surface modified carboxyl material in a mass ratio of 2:1.
[0070] Example 5
[0071] This embodiment prepares a polyester base film for photovoltaic backplane, which is different from the preparation method of Example 3 in that in step S1, Ni@ZIF-8 material and nano-silicon dioxide surface modified carboxyl material are mixed in a mass ratio of 1:1 to obtain the first filler.
[0072] Comparative Example 1
[0073] A polyester base film was prepared. The difference from Example 1 was that white ZIF-8 powder was prepared and added into PET as the first filler to prepare the upper surface layer of Comparative Example 1. The content of ZIF-8 was 1%.
[0074] Comparative Example 2
[0075] A polyester base film was prepared. The difference from Example 1 was that nano-silicon dioxide with a particle size of 40 nm was added as the first filler into PET to prepare the upper surface layer of Comparative Example 2, and the content of nano-silicon dioxide was 1%.
[0076] Comparative Example 3
[0077] A polyester base film is prepared. The difference from Example 1 is that Ni@ZIF-8 material is prepared in S1, and Ni@ZIF-8 material is mixed with PET as the first filler in S2.
[0078] Performance Testing
[0079] The base films prepared in Examples 1 to 5 and Comparative Examples 1 to 3 were subjected to the following performance tests, and the test results are recorded in Table 1.
[0080] 1. Reflectivity
[0081] The test method refers to the spectrophotometer method with an integrating sphere in the standard GB / T 29848 "Ethylene-vinyl acetate copolymer (EVA) film for photovoltaic module encapsulation", the test instrument: UV-visible spectrophotometer, test conditions: 780 ~ 1100nm.
[0082] 2. Yellowing index
[0083] The test method refers to the standard GB / T2409 "Plastic Yellowing Index Test Method"; sample size: 100x100 mm; test conditions: 25℃, 50%RH.
[0084] Table 1 Performance test results of each embodiment and each comparative example
[0085] Category Infrared light reflectivity / % Yellowing Index Example 1 79% 2.04 Example 2 77% 2.23 Example 3 86% 1.17 Example 4 83% 1.21 Example 5 81% 1.28 Comparative Example 1 8% 5.28 Comparative Example 2 46% 4.66 Comparative Example 3 77% 3.59
[0086] From the analysis of the above performance test results, it can be seen that using a mixture of ZIF-8 confined metal particle material and nano-titanium dioxide as the first filler can improve the infrared reflection performance of the polyester base film for photovoltaic backplanes and reduce its yellowing degree.
[0087] In a more preferred scheme, a material with carboxyl groups modified on the surface of nano-silicon dioxide is prepared and mixed with ZIF-8 confined metal particle material to obtain a first filler, which can further improve the dispersibility of the first filler in the upper surface, thereby further improving the infrared light reflection performance of the base film for photovoltaic backplanes.
[0088] By changing the type of metal particles confined inside ZIF-8, the mass ratio of ZIF-8 confined metal particles to the surface-modified carboxyl material of nano-silicon dioxide in the first filler and other preparation conditions, the infrared reflection effect of the metal nickel particles confined inside ZIF-8 is better than that of the confined metal silver particles. The mass ratio of ZIF-8 confined metal particles to the surface-modified carboxyl material of nano-silicon dioxide is preferably 2:1.
[0089] The polyester base film for photovoltaic backplane and the preparation method thereof of the present application are clear and easy to operate, and can obtain a polyester base film with good infrared reflection properties and anti-yellowing properties, which has practical significance.
[0090] The above describes the basic principles, main features and advantages of the present application. Those skilled in the art should understand that the present application is not limited by the above embodiments, and the above embodiments and the specification only describe the principles of the present application. The present application may have various changes and improvements without departing from the spirit and scope of the present application, and these changes and improvements fall within the scope of the present application for which protection is sought. The scope of protection claimed by the present application is defined by the attached claims and their equivalents.
Claims
1. A polyester base film for photovoltaic backsheet, characterized in that: The invention comprises an upper surface layer, a supporting layer and a lower surface layer, wherein the supporting layer is made of PET and PP, the upper surface layer is a PET material dispersed with a first filler, the lower surface layer is a PET material dispersed with a second filler, the second filler is a combination of any one or more of titanium oxide, silicon dioxide, vanadium oxide and bismuth oxide, and the first filler is a mixture of ZIF-8 confined metal particle material and nano silicon dioxide.
2. The polyester base film for photovoltaic backsheet according to claim 1, characterized in that: The first filler is a ZIF-8 confined metal particle material and a nano-silicon dioxide material in a mass ratio of (1-2):
1.
3. The polyester base film for photovoltaic backsheet according to claim 1, characterized in that: The mass percentage of the first filler in the upper surface layer is 0.5% to 1%.
4. The polyester base film for photovoltaic backsheet according to claim 1, characterized in that: The metal particles in the ZIF-8 confined metal particle material are a combination of one or more of metal platinum, metal nickel, metal palladium or metal silver.
5. The polyester base film for photovoltaic backsheet according to claim 1, characterized in that: The nano-silicon dioxide material is a nano-silicon dioxide material with surface modified carboxyl groups. The preparation method of the nano-silicon dioxide material with surface modified carboxyl groups is as follows: glutaraldehyde and (3-aminopropyl)triethoxysilane are dissolved in an organic solvent to obtain a first mixture, nano-silicon dioxide and water are added to the organic solvent to obtain a second mixture, the second mixture is added to the first mixture, and the formed precipitate is filtered, washed, and dried to obtain the nano-silicon dioxide material with surface modified carboxyl groups.
6. The polyester base film for photovoltaic backsheet according to claim 5, characterized in that: The particle size of the nano silicon dioxide is 30-60 nm.
7. The polyester base film for photovoltaic backsheet according to claim 1, characterized in that: The thickness of the upper surface layer is 60-80 μm, the thickness of the support layer is 250-350 μm, and the thickness of the lower surface layer is 25-35 μm.
8. A method for preparing a polyester base film for a photovoltaic backsheet, characterized in that: The method comprises the following preparation steps: S1: ZIF-8 is prepared using zinc salt and 2-methylimidazole, and then the ZIF-8 is added to a metal salt solution and mixed evenly to obtain a mixed solution, a reducing agent is added to the mixed solution to reduce the metal ions to metal elements, and the precipitate is filtered, dried and washed to obtain a ZIF-8 confined metal particle material; S2: mixing the ZIF-8 confined metal particle material with the nano-silicon dioxide material to form a first filler, and mixing the first filler with the PET masterbatch at high speed and then injection molding to obtain an upper surface layer; S3: Mixing PET masterbatch and PP masterbatch and then injection molding to obtain a support layer; mixing nano-silicon dioxide and PET masterbatch and then injection molding to obtain a lower surface layer; S4: co-extrude the upper surface layer, the support layer and the lower surface layer to obtain the polyester base film for the photovoltaic backsheet.
9. The method for preparing a polyester base film for a photovoltaic back sheet according to claim 8, characterized in that: When the nano-silica material is silica with surface modified carboxyl groups, the S2 step is specifically as follows: glutaraldehyde and (3-aminopropyl)triethoxysilane are dissolved in an organic solvent to obtain a first mixture, nano-silica and water are added to the organic solvent to obtain a second mixture, the second mixture is added to the first mixture, and the formed precipitate is filtered, washed, and dried to obtain the nano-silica with surface modified carboxyl groups; the ZIF-8 confined metal particle material is mixed with the nano-silica with surface modified carboxyl groups to form the first filler, and the first filler is mixed with the PET masterbatch at high speed and then injection molded to obtain the upper surface layer.
10. A photovoltaic cell, comprising, from top to bottom, a photovoltaic back sheet, a packaging material, a cell sheet, a packaging material and a packaging glass, characterized in that: The photovoltaic backplane comprises the polyester base film for photovoltaic backplane according to any one of claims 1 to 7, or the polyester base film for photovoltaic backplane prepared by any preparation method of claim 8 or 9, and the upper surface layer is arranged on a side away from the battery cell.
Citation Information
Patent Citations
Solar battery backplane and preparation method thereof
CN109801999A
Multi-layer composite solar cell backboard film and preparation method thereof
CN114023839A